Analysis of the biotopic occurrence of mouse-like rodents in the territories of natural foci of plague and tularemia in the Republic of Dagestan - E. V. Gerasimenko; A. Kh. Khalidov (Наука. Инновации. Технологии)
Mouse-like rodents in natural plague foci occupy an important place as potential reservoirs of the causative agent of this dangerous disease, acting in some cases as the main or secondary carriers of the pathogen. On the territory of the Republic of Dagestan, characterized by a variety of natural conditions – from flat dry deserts to foothills and highlands, with an abundance of anthropogenic biotopes, this group of small mammals is quite widely represented in terms of species diversity. This work is based on the analysis of the results of long-term epizootological monitoring over the period 2010–2021 carried out in three natural foci of plague: Dagestan plain-foothill, Caspian sandy and East Caucasian high-mountain and tularemia (Plain-foothill steppe, Terek-Kuma floodplain-marsh and Highmountain foothill-mountain-stream). To assess the selectivity of a species in choosing a biotope, the authors used the degree of biotopic confinement Fij (Y.A. Pesenko, 1982). All calculations were carried in Microsoft Office Excel. In these calculations, eurytopic species dominated, which can participate in the epizootic process during periods of activation of foci, contributing to the spread of infectious agents. It was revealed that most species are confined to moist biotopes of river banks and canals, which can be habitats for small mammals during periods of population depression. In this biotope, it is necessary to conduct a more thorough epizootological examination for tularemia and other particularly dangerous infections. The proposed method will make it possible to streamline the control of mouse-like rodents and optimize the work of epizootological examination on the territory of the Republic of Dagestan.